Placing knowledge: mobility in internationalised higher education - Adriansen, Hanne Kirstine; Valentin, Karen; Nielsen, Gritt B (2015)
Internationalisation of higher education is premised by a seeming paradox: On the one hand, academic knowledge strives to be universal in the sense that it claims to produce generalizable, valid and reliable knowledge that can be used, critiqued, and redeveloped by academics from all over the world; on the other hand, the rationale for strengthening mobility through internationalisation is based on an imagination of the potentials of particular locations (academic institutions). Intrigued by this tension between universality and particularity in academic knowledge production, this paper presents preliminary findings from a project that study internationalisation of higher education as an agent in the interrelated processes of place-making and knowledge-making. The project is based on three case-studies. In this paper, focus is on PhD students’ change of research environment. This is used as a case for studying what comes to count as e.g. relevant, good, true knowledge, to whom, where and why.